Association between Schistosomiasis mansoni and hepatitis C: systematic review - Daniele Silva de Moraes Van-Lume; Maria de Fatima Pessoa Militao de Albuquerque; Alexandre Ignacio de Souza; Ana Lucia Coutinho Domingues; Edmundo Pessoa de Almeida Lopes; Clarice Neuenschwander Lins de Morais; Silvia Maria Lucena Montenegro (Universidade de São Paulo, 2013)
OBJECTIVE: To perform a systematic review of the prevalence of the HCV/ S. mansoni co-infection and associated factors in Schistosoma mansoni -infected populations. METHODS: The bibliographic search was carried out using the Medline, Lilacs, SciELO, Cochrane Library and Ibecs databases. The criteria for the studies' selection and the extraction data were based on systematic review methods. Forty five studies were found, with nine being excluded in a first screening. Thirteen articles were used for data extraction. RESULTS: The HCV infection rates in schistosomiasis populations range from 1% in Ethiopia to 50% in Egypt. Several studies had poorly defined methodologies, even in areas characterized by an association between hepatitis C and schistosomiasis, such as Brazil and Egypt, which meant conclusions were inconsistent. HCV infection rates in schistosomotic populations were heterogeneous and risk factors for acquiring the virus varied widely. CONCLUSIONS: Despite the limitations, this review may help to identify regions with higher rates of hepatitis C and schistosomiasis association. However, more studies are necessary for the development of public health policies on prevention and control of both diseases.